2020
DOI: 10.1111/ssqu.12878
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Play Through Pain and Injury: An Examination of Social Learning Theory Among Iranian Athletes

Abstract: Objective This study investigates the social factors affecting playing through pain and injury of professional athletes, using Akers’s social learning theory (SLT). Methods Propositions of SLT were examined using a sample of 784 athletes from Rasht and Bandar Anzali in Iran. Results Findings from structural equation modeling indicated that the social learning components (i.e., differential association, differential reinforcement, imitations, and definitions) predicted 33 percent of the variance in athletes’ pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Playing in the face of pain and injury involves an athlete’s behavioral pattern of playing a sport even when it is likely to result in pain and injury [ 7 , 37 ]. We used three items to measure this behavior, employed in a previous publication [ 37 ]. Specifically, participants were asked to indicate (a) whether they had played through pain and injury that had threatened their overall health, (b) whether they had deliberately hidden the pain and injury that could have harmed their health and continued to play, and (c) whether they had ever endured psychological strain (fear, anxiety, distress, rumination) associated with an anticipated injury, but continued to practice and play.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Playing in the face of pain and injury involves an athlete’s behavioral pattern of playing a sport even when it is likely to result in pain and injury [ 7 , 37 ]. We used three items to measure this behavior, employed in a previous publication [ 37 ]. Specifically, participants were asked to indicate (a) whether they had played through pain and injury that had threatened their overall health, (b) whether they had deliberately hidden the pain and injury that could have harmed their health and continued to play, and (c) whether they had ever endured psychological strain (fear, anxiety, distress, rumination) associated with an anticipated injury, but continued to practice and play.…”
Section: Methodsmentioning
confidence: 99%
“…The response rate was 91.52%. Playing in the face of pain and injury involves an athlete's behavioral pattern of playing a sport even when it is likely to result in pain and injury [7,37]. We used three items to measure this behavior, employed in a previous publication [37].…”
Section: Datamentioning
confidence: 99%
“…Miller-Day and Hecht [12] define narrative as talk organized around significant or consequential experiences, with characters undertaking some action, within a context, with implicit or explicit beginning and end points and significance for the narrator or her or his audience (p. 2). Personal narratives are culturally grounded and have provided valuable insights into understanding when athletes play through pain and injury [13][14][15], how athletes interpret messages about nutrition [16], and how athletes internalize the need to detect and then self-report a concussion [17]. Past research has found that translating those insights into prevention messages featuring personal narratives can be engaging and effective in reaching youth and young adults with low awareness and/or high resistance [10,12] and provide modeling of behaviors enhancing self-efficacy [12].…”
Section: Purposementioning
confidence: 99%
“…While lifelong moderate exercise has been associated with numerous health benefits [ 2 ], participation at the elite level imposes high physical demands and increased levels of injuries [ 3 ]. It has been reported that professional athletes play through pain and injury instead of taking time to recover [ 4 ]. This practice may have negative health consequences later in life after their tennis careers are over.…”
Section: Introductionmentioning
confidence: 99%